Ethylene carbodiimide‐fixed donor splenocytes combined with α‐1 antitrypsin induce indefinite donor‐specific protection to mice cardiac allografts. (March 2017) - Lai, Xingqiang; Qiu, Longhui; Zhao, Yi; Yu, Shuangjin; Wang, Chang; Zhang, Jin; Ning, Fen; Chen, Lizhong; Chen, Guodong
Summary: Peritransplant infusion of ethylene carbodiimide‐fixed donor splenocytes (ECDI‐SPs) induces protection of islet and cardiac allografts. However, pro‐inflammatory cytokine production during the peritransplantation period may negate the effect of ECDI‐SPs. Therefore, we hypothesized that blocking pro‐inflammatory cytokine secretion while increasing levels of anti‐inflammatory cytokines would enhance the tolerance‐induced efficacy of ECDI‐SPs. The objective of this study was to determine the effectiveness of using ECDI‐SPs combined with a short course of α1‐antitrypsin (AAT) for induction of tolerance. Using a mice cardiac transplant model, we demonstrated that ECDI‐SPs + AAT effectively induced indefinite mice cardiac allograft protection in a donor‐specific fashion. This effect was accompanied by modulation of cytokines through decreasing levels of pro‐inflammatory cytokines (including IFN‐γ, TNF‐α, IL‐1β, IL‐6, IL‐17, and IL‐23) and increasing levels of anti‐inflammatory cytokines (including IL‐10, IL‐13, and TGF‐β), and by inhibition of effector T cells (Teff) and expansion of regulatory T cells (Tregs). Therefore, we concluded that combined ECDI‐SPs and AAT appeared to modulate the expression of cytokines and regulate the Teff:Treg balance to create a support milieu for graft protection. Our strategy of combining ECDI‐SPs and AAT provides a promising approach for inducing donor‐specific transplant tolerance.